Curcuminoids inhibit human and rat placental 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis. (6th April 2023) - Sang, Jianmin; Chu, Jinjin; Zhao, Xin; Quan, Hehua; Ji, Zhongyao; Wang, Shaowei; Tang, Yunbing; Hu, Zhiyan; Li, Huitao; Li, Linxi; Ge, Ren-shan
Abstract: Ethnopharmacological relevance: In traditional Chinese medicine, curcuma longa L has been applied to treat pain and tumour-related symptoms for over thousands of years. Curcuminoids, polyphenolic compounds, are the main pharmacological component from the rhizome of Curcuma longa L. Pharmacological investigations have found that curcuminoids have many pharmacological activities of anti-inflammatory, anti-tumour, and anti-metastasis. Aim of the study: 3β-Hydroxysteroid dehydrogenase (3β-HSD1) catalyses the production of steroid precursors for androgens and estrogens, which play an essential role in cancer metastasis. We explored the potency and mode of action of curcuminoids and their metabolites of inhibiting 3β-HSD1 activity and compared the species difference between human and rat. Materials and methods: In this study, we investigated the direct inhibition of 6 curcuminoids on human placental 3β-HSD1 activity and compared the species-dependent difference in human 3β-HSD1 and rat placental homolog 3β-HSD4. Results : The inhibitory potency of curcuminoids on human 3β-HSD1 was demethoxycurcumin (IC50, 0.18 μM) > bisdemethoxycurcumin (0.21 μM)>curcumin (2.41 μM)> dihydrocurcumin (4.13 μM)>tetrahydrocurcumin (15.78 μM)>octahydrocurcumin (ineffective at 100 μM). The inhibitory potency of curcuminoids on rat 3β-HSD4 was bisdemethoxycurcumin (3.34 μM)>dihydrocurcumin (5.12 μM)>tetrahydrocurcumin (41.82 μM)>demethoxycurcumin (88.10 μM)>curcumin (137.06 μM)> octahydrocurcumin (ineffective at 100 μM). Human choriocarcinoma JAr cells with curcuminoid treatment showed that these chemicals had similar potency to inhibit progesterone secretion under basal and 8bromo-cAMP stimulated conditions. Docking analysis showed that all chemicals bind pregnenolone-binding site with mixed/competitive mode for 3β-HSD. Conclusion: Some curcuminoids are potent human placental 3β-HSD1 inhibitors, possibly being potential drugs to treat prostate cancer and breast cancer. Graphical abstract: Image 1